Tool holder instrumentation for didactic purposes: a theoretical and experimental approach - Mota, João Henrique Schiavon (Universidade Federal de São Carlos, 2023)
In machining processes the feed and cut movement are the main responsible for the power consumption, justifying a deep study about it in mechanical engineering courses. The power consumption is due to the machining forces involved in these movements, related with the cutting parameters and cutting tool geometry. This relationis usually presented in machining class in a theoretical form, being made through the Orthogonal cutting theory, the Merchant’s model and the Kienzle’s model for cutting forces. This thesis first present these three theories, and aiming to provide an experimental activity for the machining classes, presents the design and instrumentation of a tool holder for measurement of machining forces. Both tool holder design and instrumentation, are present with an integrative look with other subjects of the mechanical engineering course, approaching mainly the use of materials mechanics. The tool holder was validate numerically and experimentally, pointing to a convergence between results obtained by both ways.
Instrumentação de porta-ferramentas para fins didáticos: uma abordagem teórica e experimental
Keywords: Machining; Force measurement; Cutting theories; ENGENHARIAS::ENGENHARIA MECANICA